Effects of thermal power plant ash on germination and growth of containerized Pinus pinea seedlings - Makineci, Ender; Küçük, Turan; Çalışkan, Servet (Ecological Questions, 2026)
The present study provides a novel perspective on the use of thermal power plant waste, an issue of growing importance for environmental sustainability and waste management. Specifically, it examines the effects of incorporating different proportions of thermal power plant ash (TPPA) into growing media on the germination and early development of containerized 1+0 stone pine (Pinus pinea) seedlings. The aim was to assess TPPA’s impact on germination percentage (GP), mean germination time (MGT), seedling morphology, and biomass accumulation. Six media types were prepared: 100% conventional media, 100% sand, 5%, 15%, and 30% TPPA mixed with sand, and 100% TPPA. The highest GP (81%) was observed in the 5% TPPA + 95% sand mix, declining to 54% with increasing TPPA content. Significant differences were found in most morphological traits, except for stem biomass, and the ratios of needle, above-ground, and root biomass to total biomass. Seedlings grown in the 5% TPPA + 95% sand mix showed the greatest seedling height and root length. Nitrogen content and the C/N ratio in needles varied significantly. The highest needle nitrogen was found in the 30% TPPA + 70% sand and 100% TPPA media, while the highest root nitrogen content was recorded in the 100% TPPA media. These results suggest that TPPA, particularly at low concentrations, can support healthy seedling development and may serve as a beneficial soil amendment in nurseries. Utilizing TPPA as a growing media component could offer a sustainable approach to recycling industrial waste in seedling production.